Safety and immunogenicity of a modified vaccinia Ankara vaccine using three immunization schedules and two modes of delivery: A randomized clinical non-inferiority trial. Issue 13 (23rd March 2017) - Jackson, Lisa A.; Frey, Sharon E.; El Sahly, Hana M.; Mulligan, Mark J.; Winokur, Patricia L.; Kotloff, Karen L.; Campbell, James D.; Atmar, Robert L.; Graham, Irene; Anderson, Evan J.; Anderson, Edwin L.; Patel, Shital M.; et al.
Highlights: Modified vaccinia Ankara (MVA) vaccine may be used in the event of a smallpox release. Two doses required, current schedule is administration on Days 1 and 29. More compressed schedule (Days 1 and 15 or Days 1 and 22) may allow more rapid immunity. Use of jet injectors (JI) for administration may be beneficial for mass vaccination. PRNT responses do not support condensed schedules or JI administration. Abstract: Introduction: To guide the use of modified vaccinia Ankara (MVA) vaccine in response to a release of smallpox virus, the immunogenicity and safety of shorter vaccination intervals, and administration by jet injector (JI), were compared to the standard schedule of administration on Days 1 and 29 by syringe and needle (S&N). Methods: Healthy adults 18–40 years of age were randomly assigned to receive MVA vaccine subcutaneously by S&N on Days 1 and 29 (standard), Days 1 and 15, or Days 1 and 22, or to receive the vaccine subcutaneously by JI on Days 1 and 29. Blood was collected at four time points after the second vaccination for plaque reduction neutralization test (PRNT) (primary endpoint) and ELISA (secondary endpoint) antibody assays. For each subject, the peak PRNT (or ELISA) titer was defined by the highest PRNT (or ELISA) titer among all available measurements post second vaccination. Non-inferiority of a non-standard arm compared to the standard arm was met if the upper limit of the 98.33% confidence interval of the difference in the mean log2 peak titers between the standard and non-standard arm was less than 1. Results: Non-inferiority of the PRNT antibody response was not established for any of the three non-standard study arms. Non-inferiority of the ELISA antibody response was established for the Day 1 and 22 compressed schedule and for administration by JI. Solicited local reactions, such as redness and swelling, tended to be more commonly reported with JI administration. Four post-vaccination hypersensitivity reactions were observed. Conclusions: Evaluations of the primary endpoint of PRNT antibody responses do not support alternative strategies of administering MVA vaccine by S&N on compressed schedules or administration by JI on the standard schedule. Trial Registration: clinicaltrials.gov Identifier:NCT01827371 .